Hydrophobic and stretchable Ag nanowire network electrode passivated by a sputtered PTFE layer for self-cleaning transparent thin film heaters. Issue 33 (22nd May 2018) - Lee, Sang-Mok; Kim, Sung Hyun; Lee, Jae Heung; Lee, Sang-Jin; Kim, Han-Ki
Abstract : We demonstrated hydrophobic, flexible/stretchable, and transparent electrodes made up of Ag nanowire networks passivated by a sputtered polytetrafluoroethylene layer to produce self-cleaning transparent film heaters. Abstract : We demonstrated hydrophobic, flexible/stretchable, and transparent electrodes made up of Ag nanowire (NW) networks passivated by a sputtered polytetrafluoroethylene (PTFE) layer to produce self-cleaning transparent thin film heaters (TFHs). Using carbon nanotubes and a PTFE mixed conducting target, we successfully sputtered a transparent PTFE layer on the Ag NW network using mid-frequency magnetron sputtering. The hydrophobic surface of the PTFE/Ag NW electrodes led to water-repelling and self-cleaning transparent Ag NW electrodes, which are beneficial for transparent TFH-based smart windows. Furthermore, hydrophobic PTFE/Ag NW electrodes coated on polyethylene terephthalate (PET) and polyurethane (PU) substrates showed outstanding flexibility and stretchability, respectively, due to the capping effect of the PTFE layer. Based on outer/inner bending and stretching test results, we demonstrated the superior mechanical properties of the PTFE/Ag NW electrode compared to a bare Ag NW electrode. Finally, we investigated the feasibility of the PTFE/Ag NW film coated on a PU substrate as a transparent and stretchable electrode for stretchable and self-cleaning transparent TFHs. The effective heat generation of the stretchable PTFE/Ag NW electrode indicates the potential for energy-efficient multi-functional PTFE/Ag NW-based TFHs attached to automobile windows.